Priority Based Data Dissemination in MANET - Pregizer, Florian; Sauer, Alexander (Discoveries in Agriculture and Food Sciences, 2015)
Opportunistic networks can provide network services in an infrastuctureless ad-hoc manner. This is especially useful if either no infrastructure is available or an existing infrastructure is not to be used. This can be due to high cost, or security considerations. Much effort went into the development of protocols and other theoretical background over the last decade. However use cases and applications have been neglected. In this paper we present a protocol for priority based data dissemination as well as two applications built on top of the protocol. These were implemented as Android applications on top a framework for ad-hoc communication. To show the functionality and to give some performance metrics, real world evaluations were conducted.